Pre-school education in Nigeria: discrepancies between policy and practice (2010)
The study evaluated pre-school education in Nigeria with respect to the nation's policy statements on this level of education and the extent to which the policy statements are being implemented. The variables of interest included pre-school teachers' instructional delivery modes, class size, and instructional material provision and use. The sample consisted of 93 pre-school teachers and 2859 pupils aged 4 - 5 years. Schools were selected through stratified random sampling to ensure adequate representation of private, public, urban and rural schools. Three valid and reliable classroom observational instruments were used to record instructional delivery in 216 lessons in 72 pre-primary classrooms. Data analysis involved the use of frequency, percentages, t- test, chi-square and graphical illustrations. The results revealed that teacher whole-class interaction characterized by direct instruction was the prevailing approach. Direction of communication was mainly from the teachers to the whole class, whereas the more personal ope-to-one communication between teacher and pupil occurred less frequently; use of play did not feature; the class size ranged from 8 to 99; minimal or no instructional materials were used by the teachers during teaching-learning activities. The practice, which emerged, showed that great differences exist between policy recommendations and practice on what and how pre-school programmes should be, organized in Nigeria and these may hinder our achieving the set out objectives for this level.